Life course and Temporalities of the Family: New Imaginaries, New Injunctions - Négroni, Catherine; Robin, Pierrine; Gaudet, Stéphanie (Enfances, Familles, Générations)

(untitled) (INRS-UCS, 2025)
Research framework: The research examines the misalignment of family trajectories with institutional frameworks and the temporal desynchronization of life course. The new imaginaries influencing family choices are analyzed by exploring the tensions between institutional and individual rationales. Objectives: The aim of this issue, “ Life course and Temporalities of the Family: New Imaginaries, New Injunctions, ” is to understand and analyze family changes through the concept of life course, in light of two major changes over the last 50 years: the denormalization and deinstitutionalization of life course. Methodology: The articles in this issue are underpinned by a brief review of the literature on the concept of life course, viewed in the context of some of the latest family changes. Approaches that are essentially qualitative (interviews, focus groups, observations, etc.) are drawn from different disciplinary fields: sociology, anthropology and social work. The issue is based on the research expertise of the authors who contributed to it. Results: This issue highlights the evolution of family formation, the family imaginaries that underpin it and the political norms with which it is framed. Conclusions: It appears that the new support structures proposed by the state to secure life course are failing to normalize increasingly numerous and deregulated family transitions and the desynchronization of lives. This issue shows how individuals manage both to comply with these imperatives and to turn them on their head, demonstrating innovative ways of forming a family. Contribution: The contribution of this issue is in line with a field of research that examines the life course in both the scientific and the social spheres. The issue documents ways of forming a family at a time when life course are evolving independently from institutional frameworks, while at the same time the state is attempting to regulate family trajectories. It provides information on the diverse and fragmented temporalities of family formation. The various articles show how family trajectories are structured around imagined and new constructions of the family, which manifest as individual demands to maintain control over their own life course.